Study Of Serum Levels Of Gamma- Glutamyl Transferase, Lactate Dehydrogenase, Malondialdehyde And Vitamin-E In Breast Cancer. - CHANDRAKANTH KH,; NAGARAJ,; JAYAPRAKASH MURTHY DS,; SATISHKUMAR D,; ANAND PYATI, (International Journal of Pharma and Bio Sciences, 2011)
Despite extensive research for many years throughout the world, the etiopathogenesis of cancer still remains obscure. Oxidative stress have been associated with the risk of breast cancer. A total number of 121 subjects are studied, comprising of 35 controls, 26 fibroadenoma and 60 Breast cancer subjects. Breast cancer subjects were further divided depending on stage of the cancer. Serum levels of GGT, LDH, MDA and vitamin E were estimated in all the subjects. 36 postoperative breast cancer subjects were studied. Serum GGT, LDH and MDA were significantly increased in Breast cancer and fibroadenoma when compared to controls. These levels rised significantly with severity of the Breast cancer. Postoperatively, serum GGT and LDH were increased and decreased respectively. Serum vitamin E levels decreased significantly in Breast cancer when compared to fibroadenoma and controls. Serum Gamma-glutamyl transferase and lactate dehydrogenase may be a better marker in early detection, assessing the prognosis and response to treatment along with clinical findings in Breast cancer. Determination of malondialdehyde and vitamin E may be useful in evaluating oxidative damage in patients with benign and malignant tumors of the breast.